CENTRAL RESIN PHOSPHORITE HYDROCHLORIC ACID DECOMPOSITION PRODUCTS, OBTAINING NPK-FERTILIZERS ON THE BASIS OF UREA AND POTASSIUM CHLORIDE - Zokirjon, Mamadjanov; Sobirov, Mukhtorjon (The journal of contemporary issues in business and government, 2021)
A number of scientific researches on the development of technologies for obtaining fertilizers with nitrogen, phosphorus, potassium and other nutrients on the basis of local raw materials have been organized at a high level in our country and theoretical and practical results have been achieved on the basis of wide-coverage measures on the development of economically effective methods of their application in agriculture. In this regard, it is an important task to create a technology of complex production of new varieties with high efficiency on the basis of Central Red cumin phosphates. Proceeding from this, it was studied to obtain a new type of complex fertilizers on the basis of chlorphosphoric acid porridge, urea and potassium chloride, decomposed in hydrochloric acid thermocentrate obtained from Central Redwood phosphorites.